1987
DOI: 10.1111/j.1651-2227.1987.tb10558.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Colonic Absorption of Protein Nitrogen in Infants

Abstract: The absorption of protein nitrogen by the colon was assessed in 6 infants with colostomy by giving 15N yeast protein in a dosage of 5-20 mg 15N/kg (92.4 atom-% 15N). The absorption of 15N ranged between 87.1 and 98.1% of the administered dose, and the retention in the protein pool ranged between 79.0 and 94.2%. The incorporation of 15N in the plasma proteins was demonstrated by 15N excess values between 0.02 and 0.10 atom-%. The results suggest that the colon can assimilate proteins when insufficient absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Moreover, Gargallo and Zimmerman (7) showed an improvement in whole-body nitrogen balance in pigs fed low-nitrogen diets and infused with casein into the terminal ileum. In addition, Heine et al (8) showed that when labeled yeast was infused into the colon of infants, the majority of the label that was absorbed (i.e., not excreted in feces) was retained in body protein and not excreted in urine. The results of these studies suggest that AAs are absorbed in the large intestine.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, Gargallo and Zimmerman (7) showed an improvement in whole-body nitrogen balance in pigs fed low-nitrogen diets and infused with casein into the terminal ileum. In addition, Heine et al (8) showed that when labeled yeast was infused into the colon of infants, the majority of the label that was absorbed (i.e., not excreted in feces) was retained in body protein and not excreted in urine. The results of these studies suggest that AAs are absorbed in the large intestine.…”
Section: Introductionmentioning
confidence: 98%
“…However, this belief is based on the misplaced assumption that the large bowel is effectively impermeable to amino acids. Most of the physiological studies on colonic transport have used a cleansed bowel which has absorptive characteristics very different from the unprepared bowel (Moran et al 1989 Heine et al (1987) that lSN-labelled yeast protein placed in the colon of infants could not be recovered from the effluent and about 90% was retained within the body, indicating effective absorption and retention of amino acids at the level of the colon.…”
Section: Adaptive Mechanisms : Colonic Nitrogen Metabolismmentioning
confidence: 99%
“…The colonic microflora are predominantly anaerobic and ferment carbohydrates, with the production of short-chain fatty acids of which butyrate has a significant trophic effect on the mucosa of the small intestine and colon. Also, the importance of the colon in nitrogen conservation and in nutrient absorption in patients with SBS has already been demonstrated [8][9][10].…”
Section: Discussionmentioning
confidence: 99%